A single amino acid in the PB2 gene of influenza A virus is a determinant of host range. - Subbarao, E K (1993)
The single gene reassortant virus that derives its PB2 gene from the avian influenza A/Mallard/NY/78 virus and remaining genes from the human influenza A/Los Angeles/2/87 virus exhibits a host range restriction (hr) phenotype characterized by efficient replication in avian tissue and failure to produce plaques in mammalian Madin-Darby canine kidney cells. The hr phenotype is associated with restriction of viral replication in the respiratory tract of squirrel monkeys and humans. To identify the genetic basis of the hr phenotype, we isolated four phenotypic hr mutant viruses that acquired the ability to replicate efficiently in mammalian tissue. Segregational analysis indicated that the loss of the hr phenotype was due to a mutation in the PB2 gene itself. The nucleotide sequences of the PB2 gene of each of the four hr mutants revealed that a single amino acid substitution at position 627 (Glu-->Lys) was responsible for the restoration of the ability of the PB2 single gene reassortant to replicate in Madin-Darby canine kidney cells. Interestingly, the amino acid at position 627 in every avian influenza A virus PB2 protein analyzed to date is glutamic acid, and in every human influenza A virus PB2 protein, it is lysine. Thus, the amino acid at residue 627 of PB2 is an important determinant of host range of influenza A viruses.